Equation for the solvent activity correlation in ternary electrolyte solutions - Ricardini, Andres (2013)
An analytical equation is proposed for the dependence on composition of the solvent activity of aqueous ternary electrolyte solutions. This equation was derived taking into account the limiting behaviour that must obey the solvent activity in order to be thermodynamically consistent. The correlation of experimental data corresponding to 23 ternary systems was successfully carried out. The results obtained demonstrate an excellent fitting capability of the proposed equation.